PENERAPAN RESPONSE TIME PERAWAT DALAM PELAKSANAAN PENENTUAN PRIORITAS PENANGANAN KEGAWATDARURATAN PADA PASIEN KECELAKAAN DI IGD RSD BALUNG - Dwi Surtiningsih* Cipto Susilo** Mohammad Ali Hamid** (Universitas Muhammadiyah Jember, 2016)
The philosophy emergency care that it's Live Saving Time Saving for all actions performed during emergency conditions must be really effective and efficient and the response time is calculated from the emergency care of patients come to do treatment. The condition is reminiscent of the patients losing their lives in the next three defects even very short. The purpose of this study was to identify application response time nurse in the prioritization of handling emergency accident patients in Emergency Department of Balung General Hospital. This was non-experimental research with cross sectional design. The sampling method using purposive sampling, with a population of 32 respondents in order to obtain a sample of 30 respondents. The research instrument used was the observation sheets and questionnaires. This study showed that was application response time nurse in the implementation of the prioritization of handling emergency accidents in patients with Spearman Rho significance level α = (0.001). The response time nurse in prioritization of handling emergency accident patients should be improved in order to achieve the quality of service quality to patients and families of patients who receive services. Keyword: Response time, prioritization of treatment, patient accidents